Plasmodium Perforin-Like Protein Pores on the Host Cell Membrane Contribute in Its Multistage Growth and Erythrocyte Senescence - Garg, Swati; Shivappagowdar, Abhishek; Hada, Rahul S.; Ayana, Rajagopal; Bathula, Chandramohan; Sen, Subhabrata; Kalia, Inderjeet; Pati, Soumya; Singh, Agam P.; Singh, Shailja (Frontiers in Cellular and Infection Microbiology, 2020)
The pore forming Plasmodium Perforin Like Proteins (PPLP), expressed in all stages of the parasite life cycle are critical for completion of the parasite life cycle. The high sequence similarity in the central Membrane Attack Complex/ Perforin (MACPF) domain among PLPs and their distinct functional overlaps define them as lucrative target for developing multi-stage antimalarial therapeutics. Herein, we evaluated the mechanism of Pan-active MACPF Domain (PMD), a centrally located and highly conserved region of PPLPs, and deciphered the inhibitory potential of specifically designed PMD inhibitors. The E. coli expressed rPMD interacts with erythrocyte membrane and form pores of 10.5 nm height and 24.3 nm diameter leading to hemoglobin release and dextran uptake. The treatment with PMD induced erythrocytes senescence which can be hypothesized to account for the physiological effect of disseminated PLPs in loss of circulating erythrocytes inducing malaria anemia. The anti-PMD inhibitors effectively blocked intraerythrocytic growth by suppressing invasion and egress processes and protected erythrocytes against rPMD induced senescence. Moreover, these inhibitors also blocked the hepatic stage and transmission stage parasite development suggesting multi-stage, transmission-blocking potential of these inhibitors. Concievably, our study has introduced a novel set of anti-PMD inhibitors with pan-inhibitory activity against all the PPLPs members which can be developed into potent cross-stage antimalarial therapeutics along with erythrocyte senescence protective potential to occlude PPLPs mediated anemia in severe malaria.